ANALISIS METODE YANBU’A DALAM MENINGKATKAN BACA TULIS AL-QUR’AN: (Studi di TPQ Raudlatu Usyaqil Qur’an dan TPQ Anwarul Furqon) - Lu'luil Maknunatusy Syarifah; Sa'idah, Nusrotus (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Al-Qur'an education from an early age is very important for children's development, both intellectually, physically, and mentally, because childhood is a golden phase that determines their future. The Yanbu'a method has proven to be effective in improving the ability to read the Qur'an with correct tajweed and helping children understand the meaning of the verses. This study aims to analyze the implementation of the Yanbu'a method in improving the literacy of the Qur'an in TPQ Raudlatu Usyaqil Qur'an and TPQ Anwarul Furqon. This research uses qualitative descriptive research types. The respondents to this study are the ustadz and ustadzah from TPQ Raudlatu Usyaqil Qur'an and TPQ Anwarul Furqon. Data collection was carried out using interviews, observations, and documentation. The collected data is then reduced to filter and group information based on the same theme, and then data presentation and conclusion are drawn. The results of the study show that the Yanbu'a method is effective in improving the literacy of the Qur'an students. However, there are challenges, such as parental involvement and support, as well as the varying abilities of students. The right strategy is needed to overcome the challenges in the implementation of the Yanbu'a method. The support of parents and the community proved to be an important factor in the success of the program. A structured approach and in-depth repetition are key to ensuring a good understanding of tajweed.